2022
DOI: 10.1037/pst0000380
|View full text |Cite
|
Sign up to set email alerts
|

The association between medical comorbidity and psychotherapy processes and outcomes for major depressive disorder in a community mental health setting.

Abstract: Many individuals seeking mental health services for depression often suffer from a comorbid medical condition. The goal of the present study was to assess the presence of medical comorbidity in a community mental health center setting that primarily serves a Medicare and Medicaid population, characterize the types of comorbid medical conditions experienced in this setting, and explore the association between medical conditions on the alliance, attrition from services, and outcome. Medical diagnoses were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
(88 reference statements)
1
3
0
Order By: Relevance
“…They found that approximately 70% of their sample seeking treatment for depression also had at least one medical condition, consistent with the prevalence rates reported by Fuhrmann et al (2022). King et al (2021) found that the despite the complex medical issues experienced, clients engaged in psychotherapy, developed strong therapeutic alliances, and anticipated positive treatment outcomes; they conclude that perhaps the clinicians in their study had adequate training in treating depression and medical symptoms. These first two articles of this special section are novel for their attention to psychotherapy process and outcome variables at the level of personal (i.e., patient depression, patient physical health issues) and relational (i.e., therapeutic alliance) sites of well-being when attending to both physical and mental health.…”
Section: This Special Sectionsupporting
confidence: 72%
See 1 more Smart Citation
“…They found that approximately 70% of their sample seeking treatment for depression also had at least one medical condition, consistent with the prevalence rates reported by Fuhrmann et al (2022). King et al (2021) found that the despite the complex medical issues experienced, clients engaged in psychotherapy, developed strong therapeutic alliances, and anticipated positive treatment outcomes; they conclude that perhaps the clinicians in their study had adequate training in treating depression and medical symptoms. These first two articles of this special section are novel for their attention to psychotherapy process and outcome variables at the level of personal (i.e., patient depression, patient physical health issues) and relational (i.e., therapeutic alliance) sites of well-being when attending to both physical and mental health.…”
Section: This Special Sectionsupporting
confidence: 72%
“…The second article in this part of the special section by King et al (2021) investigates the extent to which clients receiving treatment for depression in a community mental health setting experience a comorbid medical condition, and the extent to which such comorbidity is associated with the therapeutic alliance, early attrition from treatment, and treatment outcomes. They found that approximately 70% of their sample seeking treatment for depression also had at least one medical condition, consistent with the prevalence rates reported by Fuhrmann et al (2022).…”
Section: This Special Sectionmentioning
confidence: 99%
“…Research examining the benefits of psychotherapy among populations navigating physical health conditions or employed in the health care setting is needed. As described and replicated in articles within this special section (Almeida et al, 2022;Kilkus, 2022;King et al, 2021;Richey & Pointer, 2021;Piers et al, 2021), much of the literature in this area has focused on cognitive behavioral therapy. This highlights a critical need for future studies to examine the efficacy and effectiveness of other psychotherapy theories when working with populations navigating physical health issues or employed in the health care setting.…”
Section: Personalmentioning
confidence: 97%
“…This work can dovetail in future research by examining the ways in which psychotherapy constructs and processes such as the alliance (Bordin, 1976;Flückiger et al, 2018), the real relationship (Gelso, 2009;Gelso et al, 2018), and empathy (Elliott et al, 2018) are meaningful for indicators of physiological and physical health among populations navigating physical health conditions. Studies exploring these research questions will be meaningful for discerning mixed findings found in this special section related to the role of the working alliance in clients with physical health issues, including disclosure, perceived distress and burden associated with physical health, and psychotherapy outcomes (Fuhrmann et al, 2021;King et al, 2021;Piers et al, 2021).…”
Section: Relationalmentioning
confidence: 99%